Steam-Propane Injection Simulation for Heavy Oil - Astra Agus Pramana; M. Ilham Ramdhani (Penerbitan Universitas Trisakti, 2022)
This research is about Steam-Propane Injection Simulation for Heavy Oil with the aim of simulating steam-propane EOR to increase oil recovery, then knowing the effect of different injection rates and being able to describe the best scenario of each different injection. The method used is reservoir modeling using CMG STARS software. The results show that for production that only relies on natural depletion (primary recovery) for 10 years of production, only 7% recovery from OOIP is obtained and when steam-propane injection is added, oil recovery is 60-70%. For the use of different injection rates, it is known that the higher the injection rate, the faster it will reach peak production and an increase in oil recovery. The best recovery method in this case is scenario case 4 with steam-propane injection with horizontal production wells. The advantage of using additional propane injection is to accelerate peak production and increase the recovery factor.